Electrodeposition Kinetics in Li-S Batteries: Effects of Low Electrolyte/Sulfur Ratios and Deposition Surface Composition. Issue 4 (3rd March 2017) - Fan, Frank Y.; Chiang, Yet-Ming
Abstract : Lithium-sulfur batteries obtain most of their capacity from the electrodeposition of Li2 S. This is often a slow process, limiting the rate capability of Li-S batteries. In this work, the kinetics of Li2 S deposition from polysulfide solutions of 1–7 M S concentration onto carbon and two conductive oxides (indium tin oxide, ITO; and aluminum-doped zinc oxide, AZO) were characterized. Higher polysulfide concentrations were found to result in significantly slower electrodeposition, with island nucleation and growth rates up to 75% less than at low concentrations. Since Li-S batteries with low electrolyte/sulfur (E/S) ratios necessarily reach higher polysulfide concentrations during use, the present results explain why high polarization and low rate capability are observed under such conditions. Given that low E/S ratios are critical to reach high energy density, means to improve electrodeposition kinetics at high polysulfide concentrations are necessary. Towards this goal, coatings of ITO and AZO on carbon fiber current collectors were found to improve island growth rates at 5 M by up to ∼60%. Of the two oxides, AZO was found to be superior in reducing the electrodeposition overpotential. Its benefits were demonstrated for carbon fiber current collectors coated with AZO and for conductive suspensions incorporating carbon black and nanoparticle AZO.